The Word is Murder : Hawthorne #1 - Horowitz, Anthony, 1955- (New York : HarperCollinsPublishers, 2018)
When a wealthy woman is found murdered after planning her own funeral service, disgraced police detective Daniel Hawthorne and his sidekick, author Anthony Horowitz, investigate.
Keywords: Murder -- Investigation -- Fiction; Private investigators -- Fiction; Homicide -- Fiction; Criminal investigation -- Fiction; Detectives -- Fiction; Mystery fiction